LEGAL PROTECTION ON CULTURAL HERITAGE IN MALANG CITY - Diah Imaningrum Susanti (Jurnal Hukum Prasada, 2018)
Abstract Protection of cultural heritage is a nation's commitment to protect its cultural heritage. This study aims at finding the relationship between the law on cultural preservation and the law of traditional cultural expression in copyright law, especially about cultural richness and its juridical consequences and to know the application of law on cultural heritage in Malang as mandated by Law Number 11 of 2010 on Cultural Heritage. To achieve these objectives, juridical research was conducted with the orientation of two approaches, namely normative juridical to achieve the first objective, and empirical juridical to achieve the second goal. The normative approach was carried out with the stage of conducting a positive law inventory and its historical context, classification, and semantic, syntactic and phenomenological analysis. Empirical juridical research was conducted by examining how the practice of implementing the cultural heritage law in the field, namely in the city of Malang. Primary data obtained through observation and interviews with informants. Secondary data obtained from the document of education and culture of Malang City, books and related journals. Data analysis was done by triangulation with experts in the field of cultural preservation, presented in the form of description and tables. The results showed that: 1) there is an unconformity between the laws governing cultural heritage and copyright law, especially Traditional Cultural Expression. 2) In the city of Malang, the protection of cultural heritage has not been fully done since there is no Culture Preservation Ethic, Cultural Heritage Team of Malang City that can not work optimally. Keywords: Cultural Reserve, Traditional Cultural Expressions, Cultural Heritage